IMPLEMENTASI METODE PROTOTYPE DALAM SISTEM ABSENSI SISWA SMK NEGERI 1 SIKUR - Tyas, Tiya Suryaning; Afwani, Royana; Murprawati, Santi Ika; Aranta, Arik (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
The incorporation of information technology is critically important in various aspects of life, with education being no exception. Technology has demonstrated its efficacy in supporting the operations of numerous institutions, including educational establishments. Nevertheless, despite the swift progress of technology, many institutions, particularly schools, still adhere to traditional systems in their daily operations. This includes the procedure for tracking student attendance, which can result in inefficiencies. This research endeavors to address this issue by conceptualizing, constructing, and implementing a web-based system for managing student attendance, focusing on streamlining the process of recording and handling attendance data. This system utilizes web technology and a database to establish a platform, with CodeIgniter4 serving as the fundamental framework for website development, following the prototype method. The research is carried out at SMKN 1 SIKUR and the system will record student attendance data, which will be stored in the database of SMK N 1 Sikur, and is expected to replace the current method of recording student attendance. The percentage of respondents with a "strongly agree" opinion increased from 36% to 52% after the update to the previous prototype. It is hoped that further development can be undertaken to facilitate direct implementation.